PERIODS OF COLLECTION AND SIZE OF MINI-CUTTINGS IN YERBA - MATE ADVENTITIOUS ROOTING - Di Carvalho, Maria Angelica; Kratz, Dagma; da Luz, Angela; de Oliveira Fragoso, Rosimeri; Stuepp, Carlos André (Floresta, 2023)
To improve the production of yerba mate seedlings by increasing rooting rates, clonal propagation is used, especially the mini-cutting technique, which aims to increase genetic gains and production efficiency. Thus, the objective was to evaluate the influence of different sizes of mini-cuttings and successive collections on the rooting and root vigor of Ilex paraguariensis. Four successive collections were carried out and mini-cuttings measuring 4, 6, 8 and 10 cm (± 0.2) in length were made, which were staked in 110 cm 3 tubes and kept in a climate-controlled greenhouse for 45 days. Rooting percentage, number of mini-cutting roots -1 , average length of the three largest mini-cutting roots -1, callus, mortality, survival, and maintenance of original leaves were considered. Rooting was influenced by the size of the mini-cuttings, with mini-cuttings of 8 cm and 10 cm showing greater vigor. The good adaptation of the mini-stumps tends to favor the rooting of the mini-cuttings throughout the collections, showing the potential of the mini-cutting technique for the vegetative influence of Ilex paraguariensis.